Evaluation Of humoral immune response to vaccinate against infectious bronchitis (strain H120) In broiler chickens (Journal of Hama University, 2021)
The research was objected to evaluation of the Humoral Immune Response to infectious bronchitis vaccine (strain H120) In broiler chickens.Four groups of one day old broiler chickens of each group was included 100 birds.First group (control ) was unvaccinated, second group was vaccinated at 1-day-old by spray, third group was vaccinated  at 1-day-old with eye-drop, fourth group was vaccinated of 1-day-old with drinking water.The Elisa test was used to measure  antibody titres of infectious bronchitis virus in sera birds at 21 and 28 day-old.   The results were showed that antibody titres was high in second vaccinated in 1-day-old by spray as compared with third  and fourth groups at 21 and 28 day, and it was nonsignificance differences  between  second  and third groups (P > 0.05 ) and it was nonsignificance differences in antibody level at 21 and 28 day betwen  second  and fourth (P > 0.05 )  The study showed  that second group vaccined with H120 vaccine at 1-day-old by spray  vaccination was give high antibody titres as compared with other groups.